Manufacturing method of fluororesin
Patent Information
- Application Number
- JP2021049844
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-26
- Filing Date
- 2021-03-24
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-03-24
AI Technical Summary
【0014】 本発明によれば、厚みのある成形品の溶融成形を行う際の黄変が抑制されたオキソラン環を含むフッ素樹脂およびその製造方法を提供することができる。
Smart Images

Figure 0007631958000001 
Figure 0007631958000002 
Figure 0007631958000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a fluororesin and a method for producing the same. [Background technology]
[0002] Fluorine resins have excellent heat resistance, electrical properties, chemical resistance, waterproofness, liquid and oil repellency, and optical properties, so they are used in protective films for semiconductors and other electronic components, water-repellent films for inkjet printer heads, waterproof and oil-resistant coatings for filters, optical components, and more.
[0003] Among them, fluororesins containing oxolane rings have a bulky ring structure, making them amorphous and highly transparent and heat resistant. In addition, because they are composed only of carbon, fluorine, and oxygen, they have excellent electrical properties, chemical resistance, waterproofness, and liquid and oil repellency. Furthermore, because they are amorphous, they can be melt-molded.
[0004] Non-Patent Document 1 describes the synthesis and characteristics of a polymer (polyPFMMD) obtained by polymerizing perfluoro-2-methylene-4-methyl-1,3-dioxolane (PFMMD), a type of fluororesin containing an oxolane ring, using perfluorobenzoyl peroxide as a radical polymerization initiator. PolyPFMMD has excellent heat resistance. According to the study by the present inventors, the polyPFMMD described in Non-Patent Document 1 was significantly yellowed after heat melt molding, and the yellowing was particularly significant in thick molded products. Therefore, there is a strong demand for a technology that can express high transparency with less coloring even in thick molded products of polyPFMMD.
[0005] As a method for reducing the coloring of fluororesin during heating, a method for obtaining a fluororesin having an aliphatic perfluoroalkyl group terminal using an aliphatic perfluorinated initiator is known. For example, Non-Patent Document 2 reports an example of cyclopolymerization of perfluoro(butenyl vinyl ether) by bulk polymerization using (CF3CF2CF2COO)2. However, according to the study by the present inventors, even if the technology described in Non-Patent Document 2 is used for the synthesis of polyPFMMD, it cannot be said that the yellowing of polyPFMMD after heat melt molding is sufficiently reduced. In addition, the yield was extremely poor, the productivity was poor, and the molecular weight distribution Mw / Mn was large. [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] Macromolecules 2005,38,4237-4245 [Non-Patent Document 2] Journal of the Chemical Society of Japan 2001, No.12, 659-668 Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made with the aim of solving problems associated with fluororesins containing oxolane rings. Specifically, the object is to provide a fluororesin containing oxolane rings that is inhibited from yellowing after heating and melting, and that exhibits reduced coloring even when molded into thick-walled products, and a method for producing the same. [Means for solving the problem]
[0008] As a result of extensive investigations, the present inventors have found that a fluororesin containing an oxolane ring having a terminal group of a specific structure can solve the above problems, and have thus completed the present invention.
[0009] That is, the present invention relates to a fluororesin containing a residue unit represented by the following formula (1) and a terminal group represented by the following formula (2).
[0010] [ka]
[0011] (In formula (1), Rf1, Rf2, Rf3, and Rf4 each independently represent one of the group consisting of a fluorine atom, a linear perfluoroalkyl group having 1 to 7 carbon atoms, a branched perfluoroalkyl group having 3 to 7 carbon atoms, and a cyclic perfluoroalkyl group having 3 to 7 carbon atoms, and the perfluoroalkyl group may have an etheric oxygen atom, and Rf1, Rf2, Rf3, and Rf4 may be bonded to each other to form a ring having 4 to 8 carbon atoms, and the ring may contain an etheric oxygen atom.)
[0012] [ka]
[0013] (In formula (2), i is an integer of 3 to 20.) Effect of the Invention
[0014] According to the present invention, it is possible to provide a fluororesin containing an oxolane ring that is suppressed from yellowing when melt-molding a thick molded article, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The fluororesin according to one embodiment of the present invention will be described in detail below.
[0016] The fluororesin of the present invention contains a residue unit represented by the following formula (1) and a terminal group represented by the following formula (2).
[0017] [ka]
[0018] (In formula (1), Rf1, Rf2, Rf3, and Rf4 each independently represent one of the group consisting of a fluorine atom, a linear perfluoroalkyl group having 1 to 7 carbon atoms, a branched perfluoroalkyl group having 3 to 7 carbon atoms, or a cyclic perfluoroalkyl group having 3 to 7 carbon atoms, and the perfluoroalkyl group may have an etheric oxygen atom, and Rf1, Rf2, Rf3, and Rf4 may be bonded to each other to form a ring having 4 to 8 carbon atoms, and the ring may contain an etheric oxygen atom.)
[0019] [ka]
[0020] (In formula (2), i is an integer of 3 to 20.) The fluororesin of the present invention is amorphous and has high transparency and high heat resistance because it has a bulky ring structure contained in the specific formula (1). In addition, because it is composed only of carbon atoms, fluorine atoms, and oxygen atoms, it has excellent electrical properties, chemical resistance, waterproofness, and liquid and oil repellency.
[0021] In formula (1), Rf1, Rf2, Rf3, and Rf4 each independently represent one of the group consisting of a fluorine atom, a linear perfluoroalkyl group having 1 to 7 carbon atoms, a branched perfluoroalkyl group having 3 to 7 carbon atoms, or a cyclic perfluoroalkyl group having 3 to 7 carbon atoms. The perfluoroalkyl group may have an etheric oxygen atom. Rf1, Rf2, Rf3, and Rf4 may be bonded to each other to form a ring having 4 to 8 carbon atoms, and the ring may contain an etheric oxygen atom.
[0022] Examples of the linear perfluoroalkyl group having 1 to 7 carbon atoms include a trifluoromethyl group, a pentafluoroethyl group, a heptafluoropropyl group, a nonafluorobutyl group, an undecafluoropentyl group, a tridecafluorohexyl group, and a pentadecafluoroheptyl group.
[0023] Examples of the branched perfluoroalkyl group having 3 to 7 carbon atoms include a heptafluoroisopropyl group, a nonafluoroisobutyl group, a nonafluorosec-butyl group, and a nonafluorotert-butyl group.
[0024] Examples of the cyclic perfluoroalkyl group having 3 to 7 carbon atoms include a heptafluorocyclopropyl group, a nonafluorocyclobutyl group, and a tridecafluorocyclohexyl group.
[0025] Examples of the linear perfluoroalkyl group having 1 to 7 carbon atoms which may have an etheric oxygen atom include a -CF2OCF3 group, a -(CF2)2OCF3 group, and a -(CF2)2OCF2CF3 group.
[0026] Examples of cyclic perfluoroalkyl groups having 3 to 7 carbon atoms which may have an etheric oxygen atom include a 2-(2,3,3,4,4,5,5,6,6-decafluoro)-pyrinyl group, a 4-(2,3,3,4,4,5,5,6,6-decafluoro)-pyrinyl group, and a 2-(2,3,3,4,4,5,5-heptafluoro)-furanyl group.
[0027] At least one of Rf1, Rf2, Rf3, and Rf4 is preferably a fluororesin that is one type of the group consisting of a linear perfluoroalkyl group having 1 to 7 carbon atoms, a branched perfluoroalkyl group having 3 to 7 carbon atoms, or a cyclic perfluoroalkyl group having 3 to 7 carbon atoms. This allows the fluororesin of the present invention to exhibit superior heat resistance.
[0028] A specific example of the residue unit represented by formula (1) is a residue unit represented by the following formula (3).
[0029] [ka]
[0030] Among these, fluororesin containing a residue unit represented by the following formula (4) is preferred because of its excellent heat resistance and moldability, and fluororesin containing a perfluoro(4-methyl-2-methylene-1,3-dioxolane) residue unit is more preferred.
[0031] [ka]
[0032] The fluororesin of the present invention contains an end group represented by the following formula (2), which inhibits yellowing during melt molding of a thick molded product.
[0033] Here, the term "terminal group" refers to a group present at the terminal of the main chain of a polymer.
[0034] The terminal group represented by formula (2) preferably has a structure represented by the following formula (5).
[0035] [ka]
[0036] Whether the fluororesin of the present invention contains the terminal group unit represented by formula (5) can be confirmed, for example, by the following method.
[0037] That is, the solid 19 When it is confirmed that the F-NMR spectrum analysis shows peaks with maxima in the ranges of -140 ppm to 142 ppm and -143 ppm to 145 ppm, respectively, the fluororesin of the present invention can be determined to have an end group represented by formula (5). The peaks with maxima in the ranges of -140 ppm to 142 ppm and -143 ppm to 145 ppm, respectively, are assigned to -CF2- groups at the 3rd, 4th, and 5th positions of formula (5).
[0038] In addition, the solid fluorine resin 19 F-NMR measurement is a common 19For example, a Varian VNMRS-400 was used, with a magnetic field strength of 376.18 MHz (19F), a 1.6 mm FAST MAS probe, and the hahn-echo method was used, with a pulse width of 1.3 μs, a spectrum width of 250 kHz (664.6 ppm), a spectrum center: -120 ppm, a waiting time of 10 seconds, a MAS rotation speed of 39 kHz, and an accumulation count of 2048. A solid sample was measured using about 10 mg of fluororesin, with PTFE (-122.0 ppm) as the standard. 19 A method for performing F-NMR measurement can be exemplified.
[0039] The solid state of the fluororesin of the present invention 19 In F-NMR spectrum analysis, the integral value of the area of the terminal peak (6F) due to the terminal group, which shows a maximum in the range of -140 ppm to 142 ppm and -143 ppm to 145 ppm, is preferably 0.001 to 10 in total, more preferably 0.01 to 5, and even more preferably 0.05 to 5, relative to the integral value 500 of the area of the main chain peak (5F) showing a maximum at the position of -81 ppm. This further suppresses yellowing of the fluororesin. Here, the main chain peak (5F) showing a maximum at the position of -81 ppm is assigned to -CF2O- group and -CF3 group.
[0040] The fluororesin of the present invention contains a residue unit represented by formula (2) or formula (5), for example, when an oligomer of the fluororesin is solidified. 13 It can also be confirmed by C-NMR measurement. For example, oligomers dissolved in a solvent such as Zeorola H during the manufacturing process are isolated, and the solid 13 C-NMR measurement is performed. If a peak showing a maximum in the range of 90 to 92 ppm, which is derived from the F atom at the 1st position of the perfluorocycloalkyl group directly bonded to the residue unit represented by formula (1), is observed, it can be confirmed that the fluororesin contains an end group represented by formula (2) or formula (5).
[0041] The terminal group represented by formula (2) or formula (5) is preferably directly bonded to the residue unit represented by general formula (1) without any other functional group. In addition, the fluororesin of the present invention preferably does not contain a carbonyl group.
[0042] The fluororesin of the present invention has a weight average molecular weight Mw of 5×10 4 ~3×10 5 With the weight-average molecular weight Mw in this range, the melt molding processability and defoaming property when melted are excellent. Furthermore, with the weight-average molecular weight Mw in this range, the occurrence of cracks during heating and cooling is reduced. From the viewpoint of excellent melt molding processability and excellent defoaming property when melted, the fluororesin of the present invention more preferably has a weight-average molecular weight Mw of 5×10 4 ~2×10 5 It is preferable that the range is 100%.
[0043] The weight average molecular weight Mw of the fluororesin of the present invention can be calculated from the elution times of the sample and the standard sample and the molecular weight of the standard sample by using gel permeation chromatography (GPC), for example, a standard polymethylmethacrylate with a known molecular weight as the standard sample and a solvent capable of dissolving both the standard sample and the fluororesin as the eluent. An example of the solution is Asahiklin AK-225 (manufactured by Asahi Glass Co., Ltd.) to which 10 wt % of 1,1,1,3,3,3-hexafluoro-2-propanol (manufactured by Wako Pure Chemical Industries, Ltd.) has been added relative to AK-225.
[0044] The molecular weight distribution Mw / Mn, which is the ratio of the weight average molecular weight Mw to the number average molecular weight Mn of the fluororesin of the present invention, is not particularly limited, but from the viewpoints of suppressing yellowing after heating and melting, providing excellent melt molding processability, excellent defoaming properties during melting, and reducing the occurrence of cracks during heating and cooling, the molecular weight distribution Mw / Mn is preferably 1.2 to 8, more preferably 1.2 to 5, even more preferably 1.5 to 3, and even more preferably 2.0 to 3. The number average molecular weight Mn can be measured by the same method as the above-mentioned method for measuring the weight average molecular weight Mw, and the molecular weight distribution Mw / Mn can be calculated by dividing the weight average molecular weight Mw by the number average molecular weight Mn.
[0045] The fluororesin of the present invention has a yellowness index (YI) of 10 or less, more preferably 4 or less, and even more preferably 3 or less, measured in the diameter direction of a thick melt-molded product (a cylindrical molded product having a diameter of 10 mm and a height of about 17 mm, which is heated and melted in a test tube at 280°C for 24 hours and molded). According to the present inventors, compared to heating in an open environment, when a thick molded product is melt-molded in a closed environment, the yellowing of the fluororesin after heat-melt molding becomes more pronounced. As a method for evaluating the yellowness and coloration of a thick melt-molded product, for example, a method can be mentioned in which 3 g of the fluororesin of the present invention is heated in a test tube having an outer diameter of 13 mm at 280°C for 24 hours, melted, and molded to obtain a cylindrical body (diameter 10 mm and height about 17 mm) and the yellowness index (YI) is measured in the diameter direction. Here, the diameter direction is the up-down direction when the test tube is laid on its side on a desk or the like. The yellowness was measured by placing the resin molded product in a test tube, laying the test tube on its side on a sheet of white paper, taking a digital photo from above, reading the RGB values of the molded product from the image using software, and calculating the RGB values using the following formula: X=0.4124R+0.3576G+0.1805B Y=0.2126R+0.7152G+0.0722B Z=0.0193R+0.1192G+0.9505B The tristimulus values X, Y, and Z of the XYZ color system are calculated using the above formula, and the yellowness index (YI) for the C light source (auxiliary illuminant C) is calculated using X, Y, and Z in accordance with the method of JIS K7373.
[0046] The fluororesin of the present invention preferably has a yellowness index (YI) of not more than 1 in a thin melt-molded product (3 mm thick, molded by heating and melting in a petri dish at 280°C for 24 hours). The molding method and evaluation method can be those described in the Examples.
[0047] The fluororesin of the present invention may contain other monomer residue units, and examples of the other monomer residue units include tetrafluoroethylene (TFE), hexafluoropropylene (HFP), chlorotrifluoroethylene (CTFE), trifluoroethylene, hexafluoroisobutylene, perfluoroalkylethylene, fluorovinyl ether, vinyl fluoride (VF), vinylidene fluoride (VDF), perfluoro-2,2-dimethyl-1,3-dioxole (PDD), perfluoro(allyl vinyl ether), and perfluoro(butenyl vinyl ether).
[0048] Although there is no particular limitation on the particle size of the fluororesin of the present invention, the volume average particle size is preferably 1 to 1000 μm, more preferably 1 to 500 μm, and even more preferably 1 to 300 μm, because the resin powder has high fluidity, can be continuously supplied to a molding machine or the like, can be prevented from remaining in the resin, has a high bulk density, increases packing properties, and provides excellent handleability during molding.
[0049] The volume average particle size of the fluororesin of the present invention can be evaluated by particle size distribution measurement (volume distribution) by laser diffraction scattering method. The particle size distribution by laser diffraction scattering method can be measured by dispersing the resin particles in water or an organic solvent such as methanol and measuring it. As an example of a laser scattering meter, Microtrack manufactured by Microtrack Bell Co., Ltd. can be mentioned.
[0050] Volume average particle size, also known as Mean Volume Diameter, is the average particle size expressed on a volume basis. When the particle size distribution is divided into each particle size channel, the representative particle size value of each particle size channel is d, and the volume-based percentage of each particle size channel is v, it is expressed as Σ(vd) / Σ(v).
[0051] The fluororesin of the present invention is in powder form, and preferably has a volume average particle size of 1 to 1000 μm.
[0052] The method for producing a fluororesin according to one embodiment of the present invention will be described in detail below.
[0053] The fluororesin of the present invention can be produced by polymerizing a mixture containing a radical polymerization initiator represented by the following formula (6) and a monomer represented by the following formula (7).
[0054] [ka]
[0055] (In formula (6), j is an integer of 3 to 20.)
[0056] [ka]
[0057] (In formula (7), Rf5, Rf6, Rf7, and Rf8 each independently represent one of the group consisting of a fluorine atom, a linear perfluoroalkyl group having 1 to 7 carbon atoms, a branched perfluoroalkyl group having 3 to 7 carbon atoms, and a cyclic perfluoroalkyl group having 3 to 7 carbon atoms, and the perfluoroalkyl group may have an etheric oxygen atom, and Rf5, Rf6, Rf7, and Rf8 may be bonded to each other to form a ring having 4 to 8 carbon atoms, and the ring may contain an etheric oxygen atom.) Rf5, Rf6, Rf7, and Rf8 in formula (7) have the same meanings as Rf1, Rf2, Rf3, and Rf4 in formula (1), respectively.
[0058] In the method for producing a fluororesin of the present invention, by using the radical polymerization initiator represented by formula (6), a fluororesin that is suppressed from yellowing when melt-molding a thick molded product can be obtained. Furthermore, a fluororesin with a narrow molecular weight distribution Mw / Mn can be obtained. The narrow molecular weight distribution Mw / Mn improves the heat melt moldability. Furthermore, the fluororesin can be obtained with excellent yield and productivity. In addition, by using the radical polymerization initiator represented by formula (6), the radical polymerization initiator is decarboxylated and then added to the polymer, so that the obtained polymer contains almost no carbonyl groups, and the end group represented by formula (2) is directly added to the polymer, which is advantageous in obtaining a fluororesin that is suppressed from yellowing when melt-molding a thick molded product.
[0059] In the method for producing a fluororesin of the present invention, it is more preferable to use a radical polymerization initiator represented by the following formula (8). By using the radical polymerization initiator represented by the following formula (8), a fluororesin can be obtained in which yellowing during melt molding of a thick molded product is further suppressed. Furthermore, a fluororesin with a narrow molecular weight distribution Mw / Mn can be obtained. The narrow molecular weight distribution Mw / Mn improves the heat melt moldability. Furthermore, the fluororesin can be obtained with excellent yield and productivity. In this specification, the radical polymerization initiator represented by the following formula (8) is sometimes called bis(perfluorocyclohexylcarbonyl) peroxide.
[0060] [ka]
[0061] Bis(perfluorocyclohexylcarbonyl) peroxide can be obtained by the method described in JP-A-11-49749 or J.App.Polym.Sci, 1999,72,1101-1108. In this case, perfluorohexane (FC-72, 3M Japan) can be used as a solvent instead of AK-225. The bis(perfluorocyclohexylcarbonyl) peroxide of the present invention may be synthesized by a method other than the method described in the above-mentioned literature. For example, a method for synthesizing a fluorinated peroxide is described in Chem.Rev, 1996,96,1779-1808. Examples of the method include a method of reacting an acid fluoride with hydrogen peroxide, a method of reacting an acid chloride with hydrogen peroxide, and a method of reacting an acid anhydride with hydrogen peroxide. In this case, the reaction proceeds when a base such as sodium hydroxide is present in the system.
[0062] In the method for producing the fluororesin of the present invention, a chain transfer agent may be used for the purpose of adjusting the molecular weight. Examples of the chain transfer agent include organic compounds having 1 to 20 carbon atoms and containing at least one atom selected from the group consisting of hydrogen atoms and chlorine atoms. Specific examples of the chain transfer agent include organic compounds having 1 to 20 carbon atoms and containing hydrogen atoms, such as toluene, acetone, ethyl acetate, tetrahydrofuran, methyl ethyl ketone, methanol, ethanol, and isopropanol; and organic compounds having 1 to 20 carbon atoms and containing chlorine atoms, such as chloroform, dichloromethane, tetrachloromethane, chloromethane, dichloroethane, trichloroethane, tetrachloroethane, pentachloroethane, hexachloroethane, benzyl chloride, pentafluorobenzyl chloride, and pentafluorobenzoyl chloride. Among these, from the viewpoint of suppressing yellowing after heat melting, organic compounds having 1 to 20 carbon atoms and containing chlorine atoms are preferred, and organic compounds having 1 to 20 carbon atoms and containing hydrogen atoms and chlorine atoms are more preferred. The amount of the chain transfer agent is, for example, 0.01 to 50% by weight based on the total amount of the monomer and the chain transfer agent.
[0063] In the method for producing the resin of the present invention, the polymerization method is not limited, and examples thereof include solution polymerization, precipitation polymerization, bulk polymerization, emulsion polymerization, and suspension polymerization.
[0064] In the production method of the present invention, it is preferable that an organic solvent is further mixed with the mixture in the polymerization step.
[0065] In the method for producing a resin of the present invention, the resin powder has high fluidity, can be continuously supplied to a molding machine, etc., can suppress the solvent from remaining in the resin, has a large bulk density, increases packing properties, and is easy to handle during molding. Therefore, it is preferable to use an organic solvent in which at least the monomer represented by formula (7) dissolves, and at least a part of the resin produced by polymerization does not dissolve, causing precipitation of the resin, and the resin produced by polymerization precipitates in the organic solvent as particles. In the method for producing a resin of the present invention, the organic solvent may be referred to as a "precipitation polymerization solvent". By using the precipitation polymerization solvent, the resin produced by the polymerization reaction can be precipitated as particles having a specific volume average particle size, and as a result, resin particles having excellent moldability and packing properties can be produced. In addition, since no polymerization aids such as emulsifiers and dispersants are used, resin particles that do not contain emulsifiers and dispersants that cause deterioration of transparency and heat resistance can be produced.
[0066] Here, the precipitation polymerization solvent means a solvent in which the resin particles containing the residue unit represented by formula (1) remain after the resin particles are immersed in the organic solvent for a long period of time. Specifically, the weight average molecular weight Mw of the resin particles containing the residue unit represented by general formula (1) is 5×10 4 ~70×10 4When the resin particles are immersed in an organic solvent having a 10-fold amount (w / w) of the resin particles at 50° C. for 5 hours or more and the remaining resin particles can be confirmed with the naked eye in the organic solvent, the organic solvent can be regarded as the precipitation polymerization solvent A. The precipitation polymerization solvent A is preferably an organic solvent in which the weight loss rate of the resin sample remaining in a solid state is less than 20% by weight when the solution is cooled to 25° C. after immersion for 5 hours or more at 50° C. The weight loss rate of the resin sample is more preferably less than 12% by weight, and even more preferably less than 10% by weight.
[0067] The resin weight loss rate can be measured by the following method. After filtering the cooled solution, the solid on the filter is rinsed with the solvent, washed multiple times with acetone, and then dried to recover the resin sample on the filter. The weight of the recovered resin is measured, and the resin weight is subtracted from the amount of resin immersed in the organic solvent, and the result is divided by the amount of resin immersed in the organic solvent to obtain the resin weight loss rate.
[0068] Examples of the precipitation polymerization solvent include non-halogen organic solvents such as acetone, methyl ethyl ketone, hexane, and butyl acetate, chlorine-containing organic solvents such as dichloromethane and chloroform, and organic solvents containing a fluorine atom in the molecule.
[0069] Furthermore, as the precipitation polymerization solvent, an organic solvent containing fluorine atoms and hydrogen atoms in the molecule is preferable because it is difficult for chain transfer reactions to occur in radical polymerization, has excellent polymerization yield, and is easy to obtain a high molecular weight substance.Specific examples of the precipitation polymerization solvent containing fluorine atoms and hydrogen atoms in the molecule include 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 2,2,2-trifluoroethanol, 1,1,1,3,3,3-hexafluoroisopropanol, 1,2,2,3,3,4,4-heptafluorocyclopentane, 1H,1H-pentafluoropropanol, 1H,1H-heptafluorobutanol, 2-perfluorobutylethanol, 4,4,4-trifluorobutanol, 1H,1H,3H-tetrafluoropropanol, 1H,1H,5H-octafluoropropanol, 1H,1H,7H-dodecafluoroheptanol, 1H,1H,3H-hexafluorobutanol, 2 , 2,3,3,3-pentafluoropropyl difluoromethyl ether, 2,2,3,3,3-pentafluoropropyl-1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl ethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, hexafluoroisopropyl methyl ether, 1,1,3,3,3-pentafluoro-2-trifluoromethylpropyl methyl ether, 1,1,2,3,3,3-hexafluoropropyl methyl ether, 1,1,2,3,3,3-hexafluoropropyl ethyl ether, 2,2,3,4,4,4-hexafluorobutyl difluoromethyl ether, and the like.
[0070] Among them, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 2,2,2-trifluoroethanol, 1,1,1,3,3,3-hexafluoroisopropanol, and 1,2,2,3,3,4,4-heptafluorocyclopentane are preferred, and 1,2,2,3,3,4,4-heptafluorocyclopentane is preferred because it is excellent in polymerization yield and easy to obtain a high molecular weight substance. The ratio of fluorine atoms and hydrogen atoms in the molecule of the precipitation polymerization solvent is preferably fluorine atoms:hydrogen atoms=1:9 to 9:1 in terms of the number of atoms, more preferably 1:9 to 7:3, and even more preferably 4:6 to 7:3, in terms of the number of atoms, in terms of the polymerization yield. The precipitation polymerization solvent contains fluorine atoms and hydrogen atoms in the molecule, and the content of hydrogen atoms in the solvent is preferably 1% by weight or more, more preferably 1.5% by weight or more, in terms of the weight of the solvent molecule, in terms of the polymerization yield. In addition, the concentration is preferably 1% by weight or more and 5% by weight or less, more preferably 1.5% by weight or more and 4% by weight or less, in order to provide a high polymerization yield and to easily obtain a high molecular weight substance. In addition, the precipitation polymerization solvent is preferably one that does not contain a chlorine atom in the molecule, in order to provide a high polymerization yield and to easily obtain a high molecular weight substance.
[0071] The ratio of the monomer represented by formula (7) to the precipitation polymerization solvent is preferably monomer:precipitation polymerization solvent=1:99 to 50:50 by weight, more preferably 5:95 to 40:60, and even more preferably 5:95 to 30:70, in order to obtain particles with excellent productivity and flow properties.
[0072] In the production method of the present invention, it is preferable that the monomer represented by formula (7) is perfluoro(4-methyl-2-methylene-1,3-dioxolane) represented by the following formula (9), and the residue unit represented by formula (1) is a perfluoro(4-methyl-2-methylene-1,3-dioxolane) residue unit represented by formula (4).
[0073] [ka]
[0074] By producing the fluororesin according to the method of the present invention, it is possible to obtain a fluororesin that is suppressed from yellowing during melt molding of a thick molded product. Furthermore, it is possible to obtain a fluororesin with a narrow molecular weight distribution Mw / Mn while exhibiting the above properties. Furthermore, it is possible to obtain a fluororesin with excellent yield and productivity while exhibiting the above properties. EXAMPLES
[0075] The present invention will be described more specifically below with reference to examples and comparative examples, but the present invention is not limited to these.
[0076] [Measurement of weight average molecular weight Mw and molecular weight distribution Mw / Mn] Measurements were performed using gel permission chromatography equipped with a column TSKgel SuperHZM-M manufactured by Tosoh Corporation and an RI detector. The eluent used was Asahiklin AK-225 (manufactured by Asahi Glass Co., Ltd.) to which 10 wt% 1,1,1,3,3,3-hexafluoro-2-propanol (manufactured by Wako Pure Chemical Industries, Ltd.) was added. Standard polymethylmethacrylate manufactured by Agilent was used as the standard sample, and the weight average molecular weight Mw and molecular weight distribution Mw / Mn calculated in terms of polymethylmethacrylate were calculated from the elution times of the sample and the standard sample.
[0077] [solid 19 F-NMR measurements] Using a Varian VNMRS-400 with a magnetic field strength of 376.18 MHz (19F) and a 1.6 mm FAST MAS probe, the Hahn-echo method was used with a pulse width of 1.3 μs, a spectrum width of 250 kHz (664.6 ppm), a spectrum center: -120 ppm, a waiting time of 10 seconds, a MAS rotation speed of 39 kHz, and an accumulation count of 2048. The solid was measured using approximately 10 mg of fluororesin as the standard, with PTFE (-122.0 ppm). 19 F-NMR measurements were carried out.
[0078] [solid 13 C-NMR measurements] Using a Varian VNMRS-400, magnetic field strength was 100.55 MHz (13C), a 4.0 mm MAS probe was used, and the CP / MAS method was used with a spectrum width of 30.5 kHz, spectrum center: 77.5 ppm, waiting time: 3 seconds, MAS rotation speed: 10 kHz, and accumulation count of 4096. The solid was measured using approximately 50 mg of fluororesin with TMS (0 ppm) as the standard. 13 C-NMR measurements were carried out.
[0079] [Yellowness index (YI) measurement of thick melt-molded product (φ10mm×H17mm, 280℃ in test tube for 24h)] 3.0 g of fluororesin was placed in a glass test tube (ST-13M, manufactured by Nichiden Rika Glass) with an outer diameter of φ13 mm and a total length of 100 mm, the mouth of the test tube was covered with aluminum foil and an aluminum cap (M-1, manufactured by Maruemu), the tube was placed in a test tube stand, and the tube was placed in an oven and heated at 280°C for 24 hours, after which it was allowed to cool, yielding a cylindrical resin molded product in the test tube (diameter: 10 mm, height: approximately 17 mm). With the resin molded product still in the test tube, the test tube was placed on its side on a sheet of white paper, and a digital photograph was taken from above under white fluorescent light using a PowerShotSX620HS (manufactured by Canon). The RGB values of the molded product were read from the obtained image using Paint (image processing software manufactured by Microsoft). The RGB values read were calculated using the following formula: X=0.4124R+0.3576G+0.1805B Y=0.2126R+0.7152G+0.0722B Z=0.0193R+0.1192G+0.9505B The tristimulus values X, Y, and Z of the XYZ color system were calculated using X, Y, and Z. The yellowness index (YI) for light source C (auxiliary illuminant C) was calculated from X, Y, and Z according to the method of JIS K7373, and the yellowness index (YI) of a thick melt-molded product (φ10 mm × H17 mm, 280°C for 24 h in a test tube) was calculated.
[0080] [Yellowness index (YI) of thin melt-molded product (3 mm thick, in a petri dish at 280°C for 24 h)] 2.0 g of fluororesin was weighed into a petri dish with an inner diameter of 26.4 mm (a flat petri dish with a lid and a receiver made by Flat Co., Ltd., only the receiver, the glass thickness at the bottom of the receiver was 1 mm), and the petri dish was placed in an inert oven (DN411I made by Yamato Scientific Co., Ltd.), and left to stand at room temperature for 30 minutes under an air flow (20 L / min), after which the temperature was raised to 280 ° C over 30 minutes, and then heated at 280 ° C for 24 hours. Thereafter, while maintaining the air flow (20 L / min), the oven door was kept closed, the inert oven was turned off, and the sample was left to cool for 12 hours, and then the sample was taken out to obtain a fluororesin heat-melted molded product with a thickness of 3 mm and a diameter of 26.4 mm on the petri dish. At this time, air compressed by a compressor and passed through a dehumidifier (dew point temperature -20 ° C or less) was used as the air. The obtained fluororesin heat melt molded product was measured for transmittance at wavelengths of 200 nm to 1500 nm at 1 nm intervals using a spectrophotometer (U-4100 manufactured by Hitachi High-Tech Science Corporation). Data at 5 nm intervals at wavelengths of 380 nm to 780 nm were extracted from the measured transmittance data, and the tristimulus values X, Y, and Z of the XYZ color system were calculated according to the method of JIS Z8701. Furthermore, according to the method of JIS K7373, the yellowness index (YI) for the C light source (auxiliary illuminant C) was calculated, and the yellowness index (YI) of the fluororesin heat melt molded product including the petri dish was obtained. The yellowness index (YI) of the petri dish alone (receiver only) was measured, and the yellowness index (YI) of the fluororesin molded product with a thickness of 3 mm was obtained by subtracting the yellowness index (YI) of the petri dish alone (receiver only) from the yellowness index (YI) of the fluororesin molded product including the petri dish. The yellowness index (YI) of the petri dish alone (receiver only) was 0.21.
[0081] [Measurement of volume average particle size] The volume average particle diameter (unit: μm) was measured using a Microtrac MT3000 manufactured by Microtrac Bell Co., Ltd. and methanol as the dispersion medium.
[0082] [Example 1] The inside of a 3L SUS316 autoclave equipped with a paddle-type stirring blade, a nitrogen inlet tube, and a thermometer was replaced with nitrogen. A solution of 2.33g (0.0036 mol) of bis(perfluorocyclohexylcarbonyl) peroxide as an initiator dissolved in 230g of FC-72 (manufactured by 3M Japan, perfluorohexane), 175g (0.72 mol) of perfluoro(4-methyl-2-methylene-1,3-dioxolane) as a monomer, and 470g of FC-72 as a polymerization solvent were placed in an autoclave after removing dissolved oxygen, and solution polymerization was performed by maintaining the mixture at 55°C for 24 hours under stirring, to obtain a viscous liquid in which the resin was dissolved. After cooling to room temperature, the ampoule was opened, and the obtained resin solution was poured into 875g of FC-72 to adjust the viscosity, and diluted to prepare a diluted resin solution. In a plastic cup equipped with a stirring blade, 5250 g of Zeorora H (manufactured by Nippon Zeon Co., Ltd., 1,2,2,3,3,4,4-heptafluorocyclopentane, hydrogen atom content in the solvent molecule: 1.55% by weight, fluorine atoms: hydrogen atoms in the solvent molecule = 7:3 (number ratio)) was placed, and the resin dilution solution was added to the plastic cup under stirring to precipitate the resin. The precipitated resin was collected by filtration, washed twice with acetone, and vacuum dried to obtain a powdered perfluoro(4-methyl-2-methylene-1,3-dioxolane) resin (yield: 93%).
[0083] The weight average molecular weight of the obtained fluororesin was 9.5×10 4 The molecular weight distribution Mw / Mn was 3.74. The evaluation results of the fluororesin are shown in Table 1.
[0084] The solid 19 As a result of F-NMR measurement, peaks derived from the terminal perfluorocyclohexyl group were confirmed at -140.7 ppm and -143.9 ppm. The integral value of the main chain peak (5F) at -81.3 ppm was 500, while the integral value of the peak (6F) derived from the terminal group was a total of 1.46.
[0085] During the above operation, the filtrate obtained by precipitating the resin with Zeorora H was dried, and the solid was washed with acetone and dried in vacuum to obtain an oligomer.
[0086] Solids for the resulting oligomers 13 As a result of C-NMR measurement, a peak was confirmed at 91 ppm due to the F atom at position 1 of the perfluorocyclohexyl group directly bonded to the polymer end. On the other hand, no peak was observed in the carbonyl group region at 130 to 150 ppm.
[0087] [Example 2] The inside of a 3 L SUS316 autoclave equipped with a paddle-type stirring blade, a nitrogen inlet tube, and a thermometer was replaced with nitrogen.
[0088] A solution of 0.80g (0.0012 mol) of bis(perfluorocyclohexylcarbonyl) peroxide as an initiator dissolved in 80g of FC-72, 300g (1.23 mol) of perfluoro(4-methyl-2-methylene-1,3-dioxolane) as a monomer, 1120g of Zeorola-H as a polymerization solvent, and 33.33g (0.279 mol, amount of chain transfer agent: 10% by weight based on the total of monomer and chain transfer agent) of chloroform (manufactured by Wako Pure Chemical Industries, Ltd.) as a chain transfer agent were placed in an autoclave after removing dissolved oxygen, and precipitation polymerization was carried out by holding at 40°C for 24 hours under stirring to obtain a milky white slurry in which the resin precipitated in the polymerization solvent. The slurry was cooled to room temperature, and the generated resin particles were collected by filtration, washed with acetone, and vacuum dried to obtain a powdered perfluoro(4-methyl-2-methylene-1,3-dioxolane) resin (yield: 90%).
[0089] The weight average molecular weight of the obtained fluororesin was 8.8 × 10 4 The molecular weight distribution Mw / Mn was 2.48. The volume average particle size of the resulting fluororesin was 26 μm, and the powder had excellent fluidity, which was superior to that of Example 1.
[0090] [Example 3] Fluororesin solid obtained in Example 2 19As a result of F-NMR measurement, peaks derived from the terminal perfluorocyclohexyl group were confirmed at -140.2 ppm and -144.4 ppm. The integral value of the main chain peak (5F) at -81.3 ppm was 500, while the integral value of the peak (6F) derived from the terminal group was a total of 0.23.
[0091] [Comparative Example 1] In a 75mL glass ampoule, 0.173g (0.000410 mol) of bis(2,3,4,5,6-pentafluorobenzoyl) peroxide was added as an initiator, 10.0g (0.0410 mol) of perfluoro(4-methyl-2-methylene-1,3-dioxolane) was added as a monomer, and 40.0g of FC-72 was added as a polymerization solvent. The mixture was repeatedly subjected to nitrogen replacement and depressurization by freeze degassing, and then sealed under reduced pressure (monomer / solvent=20 / 80 (wt / wt)). The ampoule was placed in a thermostatic bath at 55°C and held for 24 hours to carry out radical solution polymerization, resulting in a viscous liquid in which the resin was dissolved. After cooling to room temperature, the ampoule was opened, and the resulting resin solution was poured into 50g of FC-72 to adjust the viscosity, and diluted to produce a resin dilution solution. 240 g of Zeorola H was placed in a beaker equipped with a stirrer, and the diluted resin solution was added to the beaker under stirring to precipitate the resin. The precipitated resin was collected by filtration, washed twice with acetone, and vacuum dried to obtain a lump of perfluoro(4-methyl-2-methylene-1,3-dioxolane) resin (yield 94%).
[0092] The weight average molecular weight of the obtained fluororesin was 21 × 10 4 The molecular weight distribution Mw / Mn was 2.8. The obtained fluororesin was in a lump form and had poor powder fluidity. The evaluation results of the fluororesin are shown in Table 1.
[0093] Fluororesin Solid 19 F-NMR measurement did not detect any peaks showing maxima at -140 to 142 ppm or -143 to 145 ppm. The filtrate from the resin precipitated on Zeorora H by the above procedure was dried, the solid was washed with acetone, and dried in vacuum. The obtained oligomer was then solidified. 13C-NMR showed no peaks in the region of 80 to 100 ppm, and carbonyl group peaks were detected at 139 ppm and 143 ppm.
[0094] [Comparative Example 2] A 30 mm diameter glass ampoule equipped with a magnetic stirrer was charged with 0.0865 g (0.000205 mol) of bis(2,3,4,5,6-pentafluorobenzoyl) peroxide as an initiator, 10.0 g (0.0205 mol) of perfluoro(4-methyl-2-methylene-1,3-dioxolane) as a monomer, 40.0 g of Zeorola-H (manufactured by Nippon Zeon Co., Ltd., 1,2,2,3,3,4,4-heptafluorocyclopentane) as a polymerization solvent, and 1.111 g (0.00931 mol) of chloroform (manufactured by Wako Pure Chemical Industries, Ltd.) as a chain transfer agent, and the ampoule was repeatedly subjected to nitrogen replacement by freeze degassing and depressurization, and then sealed under reduced pressure (amount of chain transfer agent: 10% by weight based on the total weight of the monomer and chain transfer agent). Precipitation polymerization was carried out by holding the ampoule upright at 55°C for 24 hours while stirring with a magnetic stirrer, resulting in a cloudy slurry in which the resin precipitated in the polymerization solvent. After cooling to room temperature, the ampoule was opened, and the liquid containing the generated resin particles was filtered, washed with acetone, and vacuum dried to obtain particulate perfluoro(4-methyl-2-methylene-1,3-dioxolane) resin (yield: 82%).
[0095] The weight average molecular weight of the obtained fluororesin was 9.6 × 10 4 The molecular weight distribution Mw / Mn was 2.6.
[0096] [Comparative Example 3] A 75 mL glass ampoule was charged with a solution of 0.52 g (0.0012 mol) of (CF3CF2CF2COO)2 as an initiator diluted with 52 g of FC-72, and 30.0 g (0.12 mol) of perfluoro(4-methyl-2-methylene-1,3-dioxolane) as a monomer. The mixture was repeatedly subjected to nitrogen replacement and depressurization by freeze degassing, and then sealed under reduced pressure. The ampoule was kept at 25°C for 24 hours to carry out radical polymerization. The ampoule was opened, and the contents were placed in a beaker containing 600 g of hexane under stirring. The solid was collected by filtration, washed twice with acetone, and dried in vacuum to obtain a lump of perfluoro(4-methyl-2-methylene-1,3-dioxolane) resin (yield 18%). The evaluation results of the fluororesin are shown in Table 1. The weight average molecular weight of the obtained fluororesin was 86 × 10 4 The molecular weight distribution Mw / Mn was 26.2. The yield was very low and the molecular weight distribution was very wide.
[0097] [Comparative Example 4] A polymerization tube equipped with a stir bar was charged with 4.8 g (0.020 mol) of perfluoro(4-methyl-2-methylene-1,3-dioxolane) as a monomer, 3 mL of dichloropentafluoropropane (AK-225, manufactured by AGC) as a solvent, 0.21 g of ammonium perfluorooctanoate as an emulsifier, 0.24 g of Na2HPO4·7H2O as a pH adjuster, 0.15 g of (NH4)2S2O8 as an initiator, and 50 mL of distilled water degassed with N2 as a solvent. The headspace above the solution was purged with N2 and then slightly pressurized with N2. The contents of the tube were then heated at 75°C for 5 h while stirring with a stir bar. The resulting reaction mixture was treated with 80 mL of aqueous HCl (6.3 M) to precipitate the polymer. The polymer was washed three times with 200 mL of distilled water and three times with 200 mL of acetone. Next, this polymer was placed in a vacuum oven and dried at 150°C under vacuum (150 mmHg) for 24 hours to obtain a white powdery polymer (yield: 3%). The above procedure from polymerization to drying was carried out two more times, and the obtained polymers were mixed to obtain a polymer for evaluation. The evaluation results of the obtained polymer are shown in Table 2. The weight average molecular weight of the obtained fluororesin was 34×10 4 The molecular weight distribution Mw / Mn was 25. The yield was very low and the molecular weight distribution was very wide. 19 F-NMR measurement revealed that no peaks showing maxima were detected at -140 to 142 ppm or -143 to 145 ppm.
[0098] [Comparative Example 5] A 75 mL glass ampoule was charged with 10.0 g (0.041 mol) of perfluoro(4-methyl-2-methylene-1,3-dioxolane) as a monomer, 35 g of AK-225 as a solvent, and 0.02 g of 4,4-bis(t-butylcyclohexyl) peroxydicarbonate (NOF Corp., Peroyl TCP) as an initiator. After repeated nitrogen replacement and depressurization by freeze degassing, the ampoule was sealed under reduced pressure. The ampoule was heated at 60°C for 3 hours while shaking in a thermostatic shaker. The polymer removed from the ampoule was dried at 100°C for 24 hours under vacuum (150 mmHg) to obtain a polymer (yield: 76%). The above-mentioned operations from polymerization to drying were carried out twice more, and the obtained polymers were mixed to obtain a polymer for evaluation. The evaluation results of the obtained polymer are shown in Table 2. The weight average molecular weight of the obtained fluororesin was 12×10 4 The molecular weight distribution Mw / Mn was 1.8. 19 F-NMR measurement revealed that no peaks showing maxima were detected at -140 to 142 ppm or -143 to 145 ppm.
[0099] [Comparative Example 6] Fluororesin solid obtained in Comparative Example 2 19 F-NMR measurement revealed that no peaks showing maxima were detected at -140 to 142 ppm or -143 to 145 ppm.
[0100] [Comparative Example 7] Fluororesin solid obtained in Comparative Example 3 19 F-NMR measurement revealed that no peaks showing maxima were detected at -140 to 142 ppm or -143 to 145 ppm.
[0101] [Table 1]
[0102] [Table 2]
[0103] [Reference example 1] The resin particles obtained in Example 2 were immersed in 10 times the amount of each of the solvents at 50° C. for 5 hours, and the presence or absence of remaining resin particles was observed with the naked eye.
[0104] The organic solvents in which residual resin particles were confirmed with the naked eye are as follows: 1,1,2,2-Tetrafluoroethyl-2,2,2-trifluoroethyl ether, 2,2,2-trifluoroethanol, 1,1,1,3,3,3-hexafluoroisopropanol, 1,2,2,3,3,4,4-heptafluorocyclopentane, chloroform.
[0105] After that, it was cooled to 25°C, filtered, and rinsed with the solvent to extract the resin particles, which were then washed twice with 10 times the amount of acetone and vacuum dried. The recovery rate was calculated from the dry weight, and in both cases the recovery rate was 90% or more. The filtrate obtained above was distilled off, and the solid content in the filtrate was calculated, and the solid content in the filtrate was less than 10% relative to the resin particles used. From the above results, it was confirmed that the weight loss rate of the resin weight was less than 10% by weight.
[0106] As shown in Examples 1 and 2, the fluororesin of the present invention has a smaller yellowness in thick melt-molded products (φ10 mm × H17 mm, 280°C for 24 h in a test tube) than Comparative Examples 1 to 3, and yellowing is suppressed even in thick molded products.
[0107] The method for producing a fluororesin of the present invention has a higher yield than the method of Comparative Example 3, and as shown in Examples 1 and 2, a fluororesin can be produced in a yield of 80% or more, and depending on the conditions, a fluororesin can be produced in a yield of 85% or more, or even 90% or more.
[0108] The fluororesin obtained by the method for producing a fluororesin of the present invention has an improved yellowness when heated in a test tube at 280°C for 24 hours, and has a narrower molecular weight distribution than the method of Comparative Example 3, with a molecular weight distribution Mw / Mn of 5 or less, and depending on the conditions, 4 or less, or even 3 or less. [Industrial Applicability]
[0109] The fluororesin of the present invention is useful in fields related to fluororesins.
Claims
1. A method for producing a fluororesin, comprising the steps of: The fluororesin contains a residue unit represented by the following formula (1) and an end group represented by the following formula (2), A method for producing a fluororesin, comprising a step of polymerizing a mixture containing a radical polymerization initiator represented by the following formula (4) and a monomer represented by the following formula (5): 【Chemistry 1】 (In formula (4), j is an integer from 3 to 20.) 【Chemistry 2】 (In formula (5), Rf 5 , Rf 6 , Rf 7 , Rf 8 each independently represents one of the group consisting of a fluorine atom, a linear perfluoroalkyl group having 1 to 7 carbon atoms, a branched perfluoroalkyl group having 3 to 7 carbon atoms, or a cyclic perfluoroalkyl group having 3 to 7 carbon atoms, the perfluoroalkyl group may have an ether oxygen atom, and Rf 5 , Rf 6 , Rf 7 , Rf 8 may be linked together to form a ring having 4 to 8 carbon atoms, and the ring may contain an ether oxygen atom. 【Chemistry 3】 (In formula (1), Rf 1 , Rf 2 , Rf 3 and Rf 4 each independently represent one of the group consisting of a fluorine atom, a linear perfluoroalkyl group having 1 to 7 carbon atoms, a branched perfluoroalkyl group having 3 to 7 carbon atoms and a cyclic perfluoroalkyl group having 3 to 7 carbon atoms, the perfluoroalkyl group may have an etheric oxygen atom, and Rf 1 , Rf 2 , Rf 3 and Rf 4 may be bonded to each other to form a ring having 4 to 8 carbon atoms, which ring may contain an etheric oxygen atom.) 【Chemistry 4】 (In formula (2), i is an integer from 3 to 20.)
2. The method for producing a fluororesin according to claim 1, wherein the radical polymerization initiator represented by formula (4) is a radical polymerization initiator represented by the following formula (6): 【Chemistry 5】
3. In the step of polymerizing, an organic solvent is further mixed into the mixture, 3. The method for producing a fluororesin according to claim 1 or 2, wherein the organic solvent is a solvent in which at least the monomer dissolves but at least a part of the resin produced by polymerization does not dissolve, causing precipitation of the resin, and the resin produced by polymerization precipitates in the organic solvent as particles.
Citation Information
Patent Citations
Perfluorocyclohexyl group-containing organic peroxide, its derivative, their use and production thereof
JP1999049749A
JP2001、
Perfluorodiacyl peroxide as polymerization initiator
JP2002332275A
Method for producing fluorine-containing polymer
JP2004059763A
Method for producing fluorine-containing 1,3-dioxolane compound, fluorine-containing 1,3-dioxolane compound, fluorine-containing polymer of fluorine-containing 1,3-dioxolane compound, and optical or electrical material using said polymer
JP2007504125A